Pengaruh Penggunaan Media Digital terhadap Motivasi Belajar Pendidikan Agama Islam Siswa di SMP Queen Alfalah 2 Ploso Mojo Kediri - Mochammad Busyro Nurul Furqon (Jurnal Al-Fatih, 2026)
This study aims to analyze the effect of digital media use on students' learning motivation in Islamic Religious Education (PAI) at Queen Alfalah 2 Middle School, Ploso Mojo, Kediri. This study was motivated by the low learning motivation of students in PAI learning which is still dominated by conventional methods. The study used a quantitative approach with a correlational design. The research sample consisted of 30 students selected through a purposive sampling technique. Data collection was carried out using a questionnaire that measured digital media use and learning motivation, while data analysis used simple linear regression. The results showed that digital media use had a positive and significant effect on students' learning motivation. This is indicated by the correlation coefficient (R) of 0.682, indicating a strong relationship, and the coefficient of determination (R²) of 0.465, meaning that 46.5% of the variation in learning motivation is influenced by digital media use. A significance value of 0.000 indicates that the effect is statistically significant. Thus, it can be concluded that the use of digital media contributes significantly to increasing students' learning motivation in Islamic Religious Education learning. Therefore, the use of digital media in learning is recommended to create a more interesting, interactive, and meaningful learning experience.